Macroeconomics without the LM: A Post-Keynesian Perspective - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
Romer (2000) provides an alternative model to the AS/AD and IS/LM models that abandons the LM schedule by having the short-term interest rate set by the central bank. His framework acknowledges the critical role of the central bank in determining short-term interest rates, which moves mainstream macroeconomics closer to Post Keynesian monetary theory. The current paper presents a Post Keynesian construction of macroeconomics without an LM schedule. Rather than describing the financial sector in terms of an exogenously determined interest rate set by the central bank, the model unpacks financial markets by fully specifying a banking sector. The key analytic feature of the Post Keynesian approach is to replace the money market with the loan market. That makes transparent the macroeconomic significance of the loan market and bank behavior, and generates an endogenous money supply driven by bank lending. If banks become more optimistic over the
urn:nbn:de:101:1-2008110445
Keywords: E12; E40; 330; bank lending; credit; endogenous money; loan market.